SOCIALIZATION OF THE PROGRAM FOR RECOVERY OF PEOPLE WITH MENTAL DISORDERS BY PUBLIC HEALTH CENTER IN LANGKAPLANCAR DISTRICT PANGANDARAN REGENCY - Yusup Sukmara; Budi Setiadi; Fachmi Syam Arifin (JGSRD: Journal of Government Science and Rural Development, 2023)
This research is motivated by several problems including: 1) There are still frequent shackles for people with mental disorders by their families in Jadikarya Village, Langkaplancar District, Pangandaran Regency. 2) The Puskesmas has not been optimal in socializing the People with Mental Disorders program so that the public's understanding of people with mental disorders is weak. 3) Lack of public concern, this is evidenced by the apathy of society towards people with mental disorders. The design of this research, the researcher uses qualitative research which is the antithesis of quantitative research. The informants in this study consisted of 4 people, namely the Head of the Langkaplancar Health Center, Responsible for Community Health Efforts for the Development of Mental Health Services at Langkaplancar Health Center, the Head of Bangunjaya Village and the Family of Patients with Mental Disorders. The results of the study showed that the socialization of the Recovery Program for People with Mental Disorders by Langkaplancar District Health Center, Pangandaran Regency in general had been carried out but was still lacking. This is evidenced by the many people with mental disorders who roam the streets, neglected and there is still violence against people with mental disorders, many people still believe in treatment using traditional methods, and there are also families of people with mental disorders who do not want to be referred to a mental hospital, the patient's family does not accept his family members experiencing mental illness. This shows that there is still a lack of socialization of the Recovery Program for People with Mental Disorders by the Langkaplancar District Health Center.